Peripheral T Cell Non-Hodgkin’s Lymphoma following Treatment of Hodgkin’s Lymphoma - Sun Hee Chang; Hye Ran Lee (Case Reports in Oncological Medicine)
Previous reports have suggested that non-Hodgkin’s lymphoma (NHL) is more likely to develop in patients with Hodgkin lymphoma (HL) compared to the general population. These two can occur synchronously or metachronously. We report here on a case of nodular sclerosis classical HL and T cell NHL that occurred in a patient metachronously. Peripheral T cell lymphoma (PTCL) of the patient was found about 2 years after treatment of classical HL. When the patient was diagnosed with HL, biopsy revealed typical RS cells, presenting positive for CD30 and CD15 and negative for CD79a and CD3 in immunohistochemistry. And PCR analysis showed IgH gene rearrangement; however, T cell receptor gene rearrangement and Epstein-Barr virus (EBV) were not detected on PCR analysis. After 2 years of treatment of HL, colonoscopic biopsy and lymph node biopsy showed CD3 positive atypical cells intermixed with small reactive lymphoid cells and plasma cells, indicating T cell lymphoma. PCR analysis demonstrated T cell receptor gene rearrangement and did not detect EBV. Although it is rare, synchronous or metachronous HL and NHL may occur. Therefore, we may need to ensure pathological confirmation, especially in case of lymphoma that did not respond to chemotherapy.